2005
DOI: 10.4103/0378-6323.13778
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-cyclophosphamide pulse therapy in systemic lupus erythematosus

Abstract: Almost all patients had good response after 3-4 pulses to allow them a normal life style. Fever, malar rash and oral ulceration responded early but photosensitivity, discoid rash, alopecia and joint pains took some more time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Dhabhai et al .,[2] in an Indian study reported significant improvement in Quality of Life (QOL) of systemic lupus erythematosus (SLE) patients only after three to four pulses. Methylprednisolone pulses were routinely given in SLE by physicians, but are expensive in Indian context.…”
Section: Introductionmentioning
confidence: 99%
“…Dhabhai et al .,[2] in an Indian study reported significant improvement in Quality of Life (QOL) of systemic lupus erythematosus (SLE) patients only after three to four pulses. Methylprednisolone pulses were routinely given in SLE by physicians, but are expensive in Indian context.…”
Section: Introductionmentioning
confidence: 99%
“…In neonates and young children, infection is usually acquired from their parents. [ 3 ] It is speculated that impaired or immature barrier function of skin of neonates, especially in preterm infants, plays an important role in acquiring dermatophyte infections during initial maternal-infant skin-to-skin contact. Furthermore, spread of dermatophytes during this very early period of life can also be assisted by immature microbiome and suboptimal immune responses.…”
mentioning
confidence: 99%
“…Among the few cases reported among neonates in the past and in a recent review of the literature of neonatal and early infantile dermatophytoses [ Table 1 ],[ 5 ] the most common organism cultured was Trichophyton rubrum . [ 2 , 3 , 5 , 6 - 8 ] Some risk factors that contribute to acquiring dermatophytosis in neonates include an active dermatophytic infection in close contacts, humid environment, epidermal immaturity, and immunosuppression. The immune system of neonates is relatively suppressed compared to that of adults.…”
mentioning
confidence: 99%